The effects of different starches and gums on instant pureed rice porridge for patients with dysphagia - Yong, Hui-Yin; Abidin, Syahariza Zainul; Rozalli, Norrazatul Hanim Mohd; Wahab, Norsila Abdul (Journal of Food Technology Research, 2023)
Dysphagia is defined as the difficulty to swallow food and liquid. Pureed food is commonly used in dysphagia management. For patients with dysphagia, a commercially available thickener is usually added during the preparation of pureed food to impart desired consistency which aids in reducing the risk of choking. However, high costs and limited availability of commercial thickener are burdens for some patients. Besides, the foods prepared by the commercial thickener also have consistent viscosity problems. Therefore, the use of instant pureed food has been proposed as an alternative solution for these shortcomings. This study was designed to evaluate the suitability of starch and gum as a thickener in instant pureed rice porridge for patients with dysphagia using rheological and sensory parameters. The experiments were then divided into two main sections: (1) analyses on rice porridge powder and (2) analyses on reconstituted rice porridge. Instant pureed rice porridge was developed for patients with dysphagia according to the framework outlined by the International Dysphagia Diet Standardisation Initiative (IDDSI). Overall, this study has successfully developed instant rice porridge that was suitable for consumption among patients with dysphagia and was proven to be acceptable through sensory study. Xanthan gum was shown to have the greatest potential to be used as a thickener in instant rice porridge. The success of the incorporation of xanthan gum into instant rice porridge can be a cheaper and more convenient option to the existing commercial thickener for dysphagia management.